Introduction to genetic analysis - Griffiths, Anthony J. F.; Doebley, John F.; Peichel, Catherine L.; Wassarman, David A. (New York : Macmillan, 2020)
"The twelfth edition of Introduction to Genetic Analysis takes this cornerstone textbook to the next level. The hallmark focus on genetic analysis, quantitative problem solving, and experimentation continues in this new edition. New to the twelfth edition are Chapter Objectives and Core Principles. Each chapter begins with a two-sentence paragraph describing the goals of the chapter and placing the chapter topic into context of the surrounding chapter. This helps students "see the forest" before stepping into the "trees". Introduction to Genetic Analysis divides genetics into three segments : transmission genetics, molecular genetics, and evolutionary genetics. Each part of the text now begins with a three- to five-page introduction outlining the core principles that characterize that segment of genetics. These help orient students by providing an overview of the themes they'll encounter as they read each part."--
Preface -- 1. The Genetics Revolution -- Part I. Core Principles in Transmission Genetics -- 2. Single-Gene Inheritance -- 3. Independent Assortment of Genes -- 4. Mapping Eukaryote Chromosomes by Recombination -- 5. Gene Interaction -- 6. The Genetics of Bacteria and Their Viruses -- Part II. Core Principles in Molecular and Developmental Genetics -- 7. DNA : Structure and Replication -- 8. RNA : Transcription, Processing, and Decay -- 9. Proteins and Their Synthesis -- 10. Gene Isolation and Manipulation -- 11. Regulation of Gene Expression in Bacteria and Their Viruses -- 12. Regulation of Transcription in Eukaryotes -- 13. The Genetic Control of Development -- 14. Genomes and Genomics -- Part III. Core Principles in Mutation, Variation, and Evolution -- 15. DNA Damage, Repair, and Mutation -- 16. The Dynamic Genome : Transposable Elements -- 17. Large-Scale Chromosomal Changes -- 18. Population Genetics -- 19. The Inheritance of Complex Traits -- 20. Evolution of Genes, Traits, and Species -- A Brief Guide to Model Organisms -- Appendix A. Genetic Nomenclature -- Appendix B. Bioinformatic Resources for Genetics and Genomics -- Glossary -- Answers to Selected Problems -- Index.
Preceded by Introduction to genetic analysis / Anthony J.F. Griffiths, Susan R. Wessler, Sean B. Carroll, John Doebley. 11th ed. c2015.
Includes index.
Keywords: Genetics -- Research; Molecular genetics; Genetics -- Methodology; Genetic Phenomena; Genetic Techniques; Genetics -- Methodology; Genetics -- Research; Molecular genetics; Genanalyse; Genetik; Textbooks; Textbooks